Surface Deformation Analysis Using Differential Interferometry Synthetics Aperture Radar in Rumpin, Cigudeg, Leuwiliang, and Cibungbulang District Period 2018-2022 - Rosse Violla Rosendrya; Budhi Setiawan (Jurnal Pendidikan Geografi Gea, 2023)
Ground movement is surface movement resulting from natural events such as landslides, earthquakes, slumping, or surface runoff. Tracking ground movement is a step in mitigating and investigating unexpected natural disasters. Administratively, the research area is in Bogor Regency, namely Rumpin, Cigudeg, Leuwiliang, and Cibungbulang Subdistricts. The area studied by the author is 9 x 9 km². The method uses more than one interferogram to capture surface topographical transformations accurately. The DInSAR method aims to extract the total phase caused by deformation by eliminating or reducing other contributing things. This study identified material movements in the form of decreases or increases. The activity of monitoring material movement is considered essential to be carried out in monitoring potential landslides in the future. SAR imagery can be used as an early warning for disaster mitigation which still requires further action, such as taking data directly to the field in the hope of getting more accuracy.